Radical neuroconstructivism: a framework to combine the how and what of teaching and learning? - Tokuhama-Espinosa, Tracey; Borja, Cynthia (Frontiers in Education, 2023)
Recent advances in pedagogical research have called attention to the dynamic nature of the teaching and learning process in which the actors mutually influence one another. The understanding of how this works in the brain --the specialized neural networks related to this process -is often limited to neuroscientists but are slowly becoming available to other learning scientists, including teachers. A transdisciplinary approach combining the best information about observable teaching-learning processes from education with newer information from the neurosciences may aid in resolving fundamental questions in the learning process.Teachers' professional formation and development is often structured in segmented topical ways (e.g., pedagogy, evaluation, planning, classroom management, social-emotional learning), to identify important content knowledge (e.g., art, reading, mathematics, STEM), or to appreciate life skills (e.g., collaboration, critical thinking, social-emotional learning). While important, knowledge about the brain, the organ responsible for learning, is typically absent from teacher education. This paper reexamines the evidence from neuroconstructivism and the hierarchy of learning trajectories and combines it with evidence from psychology and the ways humans interact during the teachinglearning process to suggest radical neuroconstructivism as a framework within which to organize teachers' professional development. The radical neuroconstructivism framework may contribute to making the content knowledge of teachers' continual professional development more visible.